Feasibility and effectiveness of a telephone-based social support intervention for informal caregivers of people with dementia: Study protocol of the TALKING TIME project - Martin Berwig; Martin Nikolaus Dichter; Bernd Albers; Katharina Wermke; Diana Trutschel; Swantje Seismann-Petersen; Margareta Halek (BMC, 2017)
Abstract Background Caring for people with dementia at home requires a significant amount of time, organization, and commitment. Therefore, informal caregivers, mainly relatives, of people with dementia often feel a high burden. Although on-site support groups are known to have positive effects on the subjective well-being (SWB) and perceived social support of informal caregivers, there are cases in which relatives have either no time or no opportunity to leave the person alone or in which there are no support groups nearby. The TALKING TIME project aims to close this supply gap by providing structured telephone-based support groups in Germany for the first time. International studies have shown benefits for informal caregivers. Methods The TALKING TIME study is a randomized controlled trial. The effects of the 3-month TALKING TIME intervention will be compared with those of a control group without intervention at two time points (baseline = T0, after 3 months = T1). The control group will receive the TALKING TIME intervention after T1. With a planned sample size of 88 participants, the study is powered to detect an estimated effect size of 0.70 for psychological quality of life, considering an α of 0.05 (two-sided), a power of 80%. Caregivers are informal caregivers who are eligible if they are 18 years of age or older and have cared for a person with diagnosed dementia for at least four hours, four days per week, in the past six months. The exclusion criteria are psychiatric disorders of the informal caregiver. The primary outcome is the mental component summary of the SF-12 rated by informal caregivers. The secondary outcomes for informal caregivers are the physical component summary of the SF-12, the Perceived Social Support Caregiver Scale (SSCS) score, and the Caregiver Reaction Scale (CRS) score. The secondary outcome for care recipients is the Neuropsychiatric Inventory (NPI-Q). For the process evaluation, different quantitative and qualitative data sources will be collected to address reach, fidelity, dosage and context. Discussion The results will provide further information on the effectiveness and optimization of telephone-based support groups for informal caregivers of people with dementia, which can help guide the further development of effective telephone-based social support group interventions. Trial registration Clinical Trials: NCT02806583 , June 9, 2016